El cuerpo reflejado. Los cuerpos dobles y los dobles corporales en la poesía española actual - Mora, Vicente Luis (Romanica Silesiana, 2021)
The portraying of the subjects in front of the looking glass is a literary topic in which the body is involved in a range of possibilities. From the corporeality of the “other” reflected by/in the narcissistic or self-critic perspective about the appearance of oneself, the mirror offers to Spanish contemporary poets a fruitful frame to explore all the variations of anagnorisis and dis-cognition. The text develops a theoretical and cultural episteme in order to read the work of a number of Spanish poets, in which the body analysed in the looking glass could adopt the form of grief, complaint, egotistical exposure, cultural references (e.g. Alice or Narcissus), or technological exam.